Genetic diversity in envelope genes of contemporary U.S. porcine reproductive and respiratory syndrome virus strains influences viral antigenicity. (December 2017) - Chen, Zhenhai; Collin, Emily; Peddireddi, Lalitha; Clement, Travis; Gauger, Phillip; Hause, Ben M.
Abstract: Porcine reproductive and respiratory syndrome (PRRS) is one of the most economically important diseases in swine caused by porcine reproductive and respiratory syndrome virus (PRRSV). Genome sequences of sixty-six PRRSV strains were obtained using metagenomic sequencing of serum samples collected in the U.S. in 2014 to explore contemporary genetic diversity. Phylogenetic analysis of the genes encoding the envelope proteins identified four to eight distinct lineages with > 87% intraclade identity. To explore the effect of the observed genetic diversity on antigenicity, the genome regions encoding either GP2a-GP3-GP4 or GP5-M in strain SD95-21 were replaced with alleles from each of eight distinct PRRSV strains using reverse genetics. The GP2a-GP3-GP4 region from only four of the eight strains yielded viable recombinant virus. When viable, both GP2a-GP3-GP4 and GP5-M variably affected antigenicity. A strain-dependent significant loss in cross reactivity was variably observed by indirect immunofluorescence assays using antisera from pigs vaccinated with commercial modified-live vaccines following replacement of GP2a-GP3-GP4 or GP5-M. Significantly reduced neutralization titers were similarly measured using antisera from naturally PRRSV-exposed pigs. These results illustrate the need to consider genomic regions besides GP5 for PRRSV epidemiology and vaccination. Highlights: Genome sequences of sixty-six PRRSV strains collected in the U.S. in 2014 were obtained using metagenomic sequencing. Phylogenetic analysis of envelope protein genes identified four to eight distinct lineages with > 87% intraclade identity. Eight chimeric viruses containing heterologous GP2a-GP3-GP4 or GP5-M genes were successfully rescued. Both GP2a-GP3-GP4 and GP5-M genes of PRRSV strains are important for virus antigenicity.